Racionais MC s: música, mídia e crítica social em São Paulo - Grecco, Anderson da Costa e Silva (2007)
Titled as The Racionais Mc`s: music, media and social criticizing in São Paulo the research aimed on presenting and analyzing the production and the constitution of the greastest rappers of the country since the biggining, the end of the 80`s boomed on the media by their social arguements and being in front of the several situations of the society. Their contestant attitude are known for about two decades and during this journey are icluded embate the media, against the repression forces of the State with the political class and also with the State itself. Their cronics were part of the ethic questions, by the capital and work relation and by the world family relationship as well. During their career, they headed their rap songs as a machine gun of social criticizing using annalize or cronics about reality experienced from their poor lives from the suburbs of São Paulo. In spite of their concequences and acts, they reached the top of the opinions division that they couldn´t neutralize their respect. On one more chapter of this great interaction of music and history, they present a work of a group that renewed the protest songs and represented a new act by making songs with no indirect or side to side criticizings. The great big deal of Racionais songs went over edges of São Paulo and named themselves as the parameter to annalize several other poor areas in Brazil, after all suburbs are suburbs